Evaluation of the antifungal activity of Morinda citrifolia L. against Aspergillus niger - Ando, Christner Margareth R. (Department of Biology and Environmental Science, College of Science, University of the Philippines Cebu, 2023)
The risks of synthetic fungicides on the environment and human health, along with emergence of fungicide-resistant fungal pathogens, emphasizes the need to develop a natural, nontoxic, and environment-friendly antifungal agent. This study was conducted with specific objective to evaluate the antifungal activity of the leaf and root bark extract of Morinda citrifolia. The study assessed the antifungal activity of the M. citrifolia extracts against a major fungal pathogen, A. niger ATCC 3080. The antifungal activity of the extracts was assessed at different concentrations (150, 350, 550, 750, mg/mL abd the inhibition zones were compared with the 30 mg/mL Nystain. The results from the assay showed that the Noni root bark has a concentration-dependent bioactivity against A. niger ATCC 3080 but not the leaves. Specifically, all concentrations exhibited an inhibition zone against A. niger ATCC 3080 throughout the seven days of oberservation except for 150 mg/mL. A phytochemical screening was able to determine the presence of alkaloids, flavonoids, phenols, terpenoids, and saponins which were reported from rpevious literatures to be associated with antimicrobial effects. The result of the antifungal assay found that the Noni root bark extract showed no signififcant difference from the positive control at high concentrations thus, the Noni root bark can be a potential source of bioactive compounds that can be further developed into new fungicides or antifungal drugs.